Diversity, Evenness, and Species Richness of Aerial Insects in Dry Land of Kefamenanu, North Central Timor, East Nusa Tenggara - Amrulloh, Mohamad Fajar Farid; Kamaludin, Kamaludin; Atini, Blasius; Priyambodo, Hernur Yoga; Moi, Maria Yasinta (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 3 (2022): ATBES, 2022)
This research was conducted to determine the diversity, richness, and evenness of aerial insects based on habitat characteristics in the dry land of Kefamenanu city, North Central Timor, East Nusa Tenggara. The research was conducted on three types of habitats, namely dry land, rivers, and lakes by purposive sampling method. Sampling was done by documenting specimens in each habitat, identifying, inventorying, and analyzing quantitatively to obtain data on species diversity, species richness, and species evenness. Results revealed that aerial insects in Kefamenanu City were found in 9 orders, 25 families, 44 genera, 54 species, and 1998 individuals in three habitat types with diversity index (H'=3,068), evenness index (E=0.774), richness index (R). = 6.974), and dominance index (0.074). Aerial insects in dryland habitats are found in 8 orders, 18 families, 32 genera, 32 species, 514 individuals with diversity index (H'=2.735), evenness index (E=0.789), richness index (R=4.966), and dominance index. (0.092). Aerial insects in river habitat found 7 orders, 20 families, 40 genera, 47 species, and 792 individuals with diversity index (H'=3.205), evenness index (E=0.833), richness index (R=6.892), and dominance index (0.075). Aerial insects in the lake habitat found 8 orders, 18 families, 35 genera, 39 species, 692 individuals with diversity index (H'=2,906), evenness index (E=0.793), richness index (R=5.811), and dominance index (0.083).